Psoriasis and Cardiovascular Diseases: An Immune-Mediated Cross Talk? - Orlando, Gloria; Molon, Barbara; Viola, Antonella; Alaibac, Mauro; Angioni, Roberta; Piaserico, Stefano (Frontiers in Immunology, 2022)
Psoriasis is a worldwide spread chronic immune mediated inflammatory skin disease, characterised by well-demarcated scaly, erythematous, infiltrated plaques. The cutaneous-to-systemic expansion of the inflammation in psoriasis leads to the concept of “psoriatic march” or “inflammatory skin march”. Accordingly, psoriasis is increasingly thought to be a systemic inflammatory disease associated with numerous co-morbidities. Indeed, it’s currently considered an independent risk factor for cardiovascular diseases (CVDs). Here, we discuss the current knowledge on TNF- and IL-23/IL-17 mediated pathways linking the psoriatic plaque to the cardiovascular compartment. We further argue the possible involvement of the endothelial compartment in the psoriatic plaque- cardiovascular system crosstalk.